A Stacked Ensemble Deep Learning Approach For Imbalanced Multi-class Water Quality Index Prediction - Wen Yee Wong; Khairunnisa Hasikin; Anis Salwa Mohd Khairuddin; Sarah Abdul Razak; Hanee Farzana Hizaddin; Mohd Istajib Mokhtar; Muhammad Mokhzaini Azizan (Tech Science Press, 2024)
Indexed by WOS/Scopus/ERA